Activité antibactérienne de l’huile essentielle de deux épices : Syzygium Aromaticum et Illicium Verum. - Boukhatem, Fadhila (My University, 2017)
Essential oils possess significant antimicrobial activity and can substitute. With success to antibiotics that show their inefficiencies against resistant microorganisms, this led us to carry out a chemical analysis and study of the antimicrobial activity of essential oils of syzygum aromaticum and illicium verum. The chemical analysis of the three extracts: macerated, decoction and infused of both spices revealed the presence of flavonoids, condensed tannins and polyphenol. The total content of phenolic compound was determined using the Folin-Ciocalteu reagent, Is 200 μg EAC / mg Ps for Syzygium Aromaticum and 102.939 μg EAC / mg Ps for that of Illicium verum. Flavonoids were evaluated using the AlCl3 method, their contents being 25.611 μg EQ /mg Extract of Syzygium Aromaticum and 40.995 μg EQ /mg Ps for Illicium verum. Extraction of the essential oil by steam distillation showed a significant yield of 4.58% for Illicium verum (L) and 3.302% for Syzgyium Aromaticum (L). The antimicrobial activity was determined on two pathogenic bacterial strains, according to the disk diffusion method. The essential oil of Syyzgium Aromaticum (clove) has a strong antibacterial activity represented with inhibition diameters varying between 11 mm to 16 mm against Escherichia coli and 8 mm to 14 mm for Pseudomanas auroginosa.
Keywords: Syzgyium Aromaticum; Illicium verum; analyse chimique; activité antibactérienne.; chemical analysis; antibacterial activity.